Examining motor evoked potential amplitude and short‐interval intracortical inhibition on the up‐going and down‐going phases of a transcranial alternating current stimulation (tacs) imposed alpha oscillation. (5th February 2021) - Vallence, Ann‐Maree; Dansie, Kathryn; Goldsworthy, Mitchell R.; McAllister, Suzanne M.; Yang, Ruiting; Rothwell, John C.; Ridding, Michael C.
Abstract: Many brain regions exhibit rhythmical activity thought to reflect the summed behaviour of large populations of neurons. The endogenous alpha rhythm has been associated with phase‐dependent modulation of corticospinal excitability. However, whether exogenous alpha rhythm, induced using transcranial alternating current stimulation (tACS) also has a phase‐dependent effect on corticospinal excitability remains unknown. Here, we triggered transcranial magnetic stimuli (TMS) on the up‐ or down‐going phase of a tACS‐imposed alpha oscillation and measured motor evoked potential (MEP) amplitude and short‐interval intracortical inhibition (SICI). There was no significant difference in MEP amplitude or SICI when TMS was triggered on the up‐ or down‐going phase of the tACS‐imposed alpha oscillation. The current study provides no evidence of differences in corticospinal excitability or GABAergic inhibition when targeting the up‐going (peak) and down‐going (trough) phase of the tACS‐imposed oscillation. Abstract : The endogenous alpha rhythm has been associated with phase‐dependent modulation of corticospinal excitability. The current study provides no evidence of differences in corticospinal excitability or GABAergic inhibition when targeting the up‐going (peak) and down‐going (trough) phase of the transcranial alternating current stimulation (tACS) imposed oscillation. Future work should examine the effect of tACS intensity, duration and frequency on alpha power and phase synchronization to determine whether tACS can entrain the endogenous alpha oscillation.